Tuber melanoexcavatum sp. nov., an edible black truffle from China - Wang, Li; Tang, Song-Ming; Zhang, Xiaolei; Su, Kaimei; Li, Yongjun; Yuan, Tianjun; Wang, Yun; Dauner, Lucas; Li, Shuhong (Phytotaxa, 2020)
A new black truffle species with a basal cavity, Tuber melanoexcavatum, is identified and described. The new species is morphologically similar to T. pseudobrumale, T. pseudoexcavatum, and T. mesentericum in having a basal cavity. However, T. melanoexcavatum differs from T. pseudobrumale and T. pseudoexcavatum in having black pyramidal warts and 5 to 8 spored asci, and differs from T. mesentericum by having spiny ascospores and 1 to 5 spored (rarely 6 spored) asci. Phylogenetic analysis indicates that T. melanoexcavatum is most closely related to T. pseudobrumale, but the two still clearly differentiate. Tuber melanoexcavatum grows as a mycorrhizal association with Cyclobalanopsis glaucoides. Tuber melanoexcavatum is considered an edible black truffle species and is indigenous to China.